PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE THINK PAIR SHARE (TPS) TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 42 PADANG - Aprilla Silfa Khotimah; Andria Catri Tamsin (EDU RESEARCH, 2024)
This research uses an experimental method with a Posttest Only Control Group design. The research population was 130 students in class VIII of SMP Negeri 42 Padang, with samples selected using purposive sampling: class VIII.2 as the control class (32 students) and class VIII.3 as the experimental class (33 students). The research variables include explanatory text writing skills without and with the Think Pair Share (TPS) model. Data is collected through performance tests. The research results show: (1) writing skills without TPS are in the Almost Sufficient category with an average of 55.21; (2) writing skills with TPS are in the More than Adequate category with an average of 66.92; (3) The t test shows a significant effect of the TPS model on writing skills (t_table < t_count, 1.79 < 16.1). The TPS model can be an alternative for learning to write explanatory texts.